Estabelecimento de protocolos para a criopreservação de tecido testicular de catetos (pecari tajacu linnaeus, 1758) - Silva, Andréia Maria da (Universidade Federal Rural do Semi-Árido, 2019)
Cryopreservation of male gonadal tissue can be used in the conservation of genetic material, in order to form a germplasm bank allowing the maintenance of genetic variability in prepubertal and adult animals. Therefore, the aim was to establish an efficient protocol for cryopreservation of testicular tissue of collared peccaries. Therefore, the study was divided into two experiments, using 10 adult animals, 5 for each experiment, from the UFERSA Center for Wild Animals Multiplication. In experiment I, five pairs of testicles were fragmented (9 mm3) and allocated to non-vitrified (control) and vitrified solid-surface (SSV) groups following exposure to different cryoprotectants (3.0 M dimethyl sulfoxide (DMSO), 3.0 M ethylene glycol (EG) or 1.5 M DMSO/1.5 M EG). After warming, samples were evaluated for histomorphology, ultrastructure, viability, and proliferative capacity potential. The appropriate conservation of the ultrastructural organization of the seminiferous tubule in terms of lumen presence and cell junctions was only observed at the use of DMSO/EG combination. Regardless of the cryoprotectant, the vitrification effectively preserved cell nuclear visualization and condensation similarly as observed at the non-vitrified group. Moreover, DMSO/EG combination provided a better preservation of basal membranes of seminiferous tubules than DMSO (P < 0.05). Only the DMSO/EG combination maintained the proliferative capacity potential for spermatogonia (3.69 Nucleolus Organizing Regions - NORs/cell) and Sertoli cell (3.19 NORs/cell) similar to controls (3.46 and 3.31 NORS/cell, respectively). In conclusion, DMSO/EG in combination is better than DMSO or EG alone for SSV of testicular tissue biopsies from adult collared peccaries. In experiment II, five pairs of testicles were also fragmented (3 mm3) and allocated to non-cryopreserved (control) and cryopreserved groups using three cryopreservation methods: slow freezing (SF), cryotube vitrification (CV) and solid surface vitrification (SSV), and then exposed to different combinations of cryoprotectants (1.5 M DMSO/1.5 M EG, 1.5 M DMSO/1.5 M glycerol - G, and 1.5 M G/1.5 M EG). Non-cryopreserved and cryopreserved samples were evaluated for histomorphology, viability, proliferative potential and DNA fragmentation. Only in the use of DMSO/EG during SF and CV, it was possible to preserve DNA integrity in a similar way to control (P> 0.05). In addition, it was observed that, regardless the cryopreservation method, the DMSO/EG and DMSO/G combinations were able to preserve viability (P> 0.05). All treatments maintained the proliferative capacity potential for spermatogonia in a similar manner; however, G/EG in the SF and SSV methods impaired the proliferative potential of Sertoli cells (P> 0.05). Finally, the SF protocol using the DMSO/EG or DMSO/G combinations were better at preventing edema than G/EG for SF and DMSO/ G for SSV (P <0.05). In conclusion, we suggest the use of a DMSO/EG combination associated with slow freezing or vitrification in cryotubes for cryopreservation of testicular tissue of adult peccaries.
Keywords: Biobanco; Germoplasma; Testículo; Célula germinativa; Biobank; Germplasm; Testicle; Germ cell; CIENCIAS AGRARIAS::AGRONOMIA